2009
DOI: 10.1111/j.1574-6976.2008.00135.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of virulence and antibiotic resistance by two-component regulatory systems inPseudomonas aeruginosa

Abstract: The Gram-negative opportunistic pathogen Pseudomonas aeruginosa ubiquitously inhabits soil and water habitats and also causes serious, often antibiotic resistant, infections in immunocompromised patients (e.g. cystic fibrosis). This versatility is mediated in part by a large repertoire of two-component regulatory systems that appear instrumental in the regulation of both virulence processes and resistance to antimicrobials. Major two-component regulatory system proteins demonstrated to regulate these diverse p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
270
0
15

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 292 publications
(288 citation statements)
references
References 115 publications
(161 reference statements)
3
270
0
15
Order By: Relevance
“…This result is to be expected because the synthesis of EPS is a stationaryphase, gene-dependent process and the GacS/GacA TCS has been shown to regulate the expression of multiple phenotypes, including the production of virulence factors, A. Tahrioui, E. Quesada and I. Llamas enzymes, antibiotics and polymers (Gooderham & Hancock, 2009). This regulation may take place directly, as it does in Azotobacter vinelandii, with GacA activating the synthesis of polymers, alginate and poly-b-hydroxybutyrate (PHB) by regulating the expression of rpoS, which in turn controls stationary-phase functions (Castañeda et al, 2000(Castañeda et al, , 2001Hernandez-Eligio et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This result is to be expected because the synthesis of EPS is a stationaryphase, gene-dependent process and the GacS/GacA TCS has been shown to regulate the expression of multiple phenotypes, including the production of virulence factors, A. Tahrioui, E. Quesada and I. Llamas enzymes, antibiotics and polymers (Gooderham & Hancock, 2009). This regulation may take place directly, as it does in Azotobacter vinelandii, with GacA activating the synthesis of polymers, alginate and poly-b-hydroxybutyrate (PHB) by regulating the expression of rpoS, which in turn controls stationary-phase functions (Castañeda et al, 2000(Castañeda et al, , 2001Hernandez-Eligio et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Among TCSs the GacS/GacA system is well preserved in a variety of Gram-negative bacterial genera, such as Acinetobacter, Azotobacter, Erwinia, Escherichia, Legionella, Pseudomonas, Salmonella, Serratia and Vibrio. The GacS/GacA TCS has been reported to regulate an array of phenotypes such as the production of virulence factors, plant-growth promotion, swarming motility, biofilm formation, exopolysaccharide (EPS) biosynthesis, production of secondary metabolites and quorum sensing (QS) signal molecules and the secretion of proteins and enzymes (Gooderham & Hancock, 2009;Heeb & Haas, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…We have shown that LpxOdependent lipid A modification is not only important for Klebsiella survival in the lung but also mediates resistance to the clinically relevant AP colistin. The connection between virulence and antibiotic resistance has been particularly studied in the case of Pseudomonas (40,41). A number of bacterial regulatory genes have been identified to influence both virulence and antibiotic resistance including PhoPQ (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…They consist of a sensor histidine kinase and a transcriptional activator (Gooderham & Hancock, 2009;Rodrigue et al, 2000). PhoP-PhoQ is one such two-component regulatory system, which has been identified as important for virulence in several Enterobacteriaciae but has yet to be linked to virulence in P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%